PENGARUH EARNING PER SHARE (EPS) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PT. BANK CENTRAL ASIA (BCA) TBK. YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2013-2022 - Monika Manalu, Siska; Akbar, Akhmad (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of Earning Per Share and Return On Equity on Share Prices at PT. Bank Central Asia (BCA), Tbk for the period 2013-2022. The independent variables in this research are Earning Per Share and Return On Equity while the dependent variable used is Share Price. This research was conducted using secondary data and quantitative descriptive methods with an associative approach. This research population uses data, namely financial reports, with samples namely balance sheets and profit and loss reports as well as share price reports for 10 years (2013-2022). The data analysis techniques used are descriptive statistical analysis, classical assumption test, coefficient of determination test, multiple linear regression test and hypothesis testing (t test and F test). The results of this study show that Earning Per Share partially does not have a significant effect on share prices, seen from the significant value greater than 0.05 where the value is 0.191 > 0.05 while the tcount value shows results that are smaller than ttable of -1.448 < 2.365 and The Return On Equity variable partially has an insignificant effect on Share Prices where the significant value is greater than 0.05, namely 0.144 > 0.05 and the t value shows that it is smaller than t table, namely -1.643 > 2.365. Meanwhile, simultaneously Earning Per Share and Return On Equity have a significant effect on Share Prices, where the result is a significant value of 0.036 < 0.05, while the results of the Fcount test show it is greater than Ftable, namely 5.580 > 4.737.